Estimating the cost of caring for people with cancer at the end of life: A modelling study. (December 2015) - Round, Jeff; Jones, Louise; Morris, Steve
Background: People with advanced cancer require a range of health, social and informal care during the final phases of life. The cost of providing care to this group as they approach the end of their lives is unknown, but represents a significant cost to health and social care systems, charities patients and their families. Aim: In this study, we estimate the direct and indirect costs for lung, breast, colorectal and prostate cancer patients at the end of life (from the start of strong opioids to death) in England and Wales. Methods: We use a modelling-based approach to estimate the costs of care. Data are estimated from the literature and publicly available data sets. Probabilistic sensitivity analysis is used to reflect uncertainty in model estimates. Results: Total estimated costs for treating people with these four cancers at the end of life are £641 million. Breast and prostate cancer patients have the highest expected cost per person at £12, 663 (95% credible interval (CI): £1249–£38, 712) and £14, 859 (95% CI: £1391–£46, 424), respectively. Lung cancer has the highest expected total cost (£226m). The value of informal care giving accounts for approximately one-third of all costs. Conclusion: The cost to society of providing care to people at the end of their lives is significant. Much of this cost is borne by informal care givers. The cost to formal care services of replacing this care with paid care giving would be significant and demand for care will increase as the demographic profile of the population ages.